Design-Based Learning in Undergraduate Engineering Education: A Systematic Conceptual Review of Implementation, Impact, and Challenges - Fang, Chen; Dantes, Gede Rasben; Dantes, Kadek Rihendra; Wahyuni, Dessy Seri (PPSDP International Journal of Education, 2025)
This conceptual review synthesises and critically analyses recent literature on Design-Based Learning (DBL) in undergraduate engineering education. It examines how DBL is defined, how it is implemented and assessed, what strengths and recurring challenges are reported, and what these imply for teaching, programmes, and future research. A document-based search in Scopus, Web of Science, and Google Scholar identified English, peer-reviewed studies published between 2018 and 2024; a small number of earlier design-oriented works were retained to anchor key concepts. The review shows that DBL is characterised by iteration on an authentic design brief, structured reflection, and collaboration, and that when these elements and their assessment are explicit, DBL supports student engagement, problem solving, and the early formation of engineering identity. It also notes implementation problems across settings, especially heavy assessment load, limited opportunity for multiple iterations within fixed timetables, and team tasks that reproduce participation hierarchies. By isolating DBL’s pedagogical identity from related approaches such as PBL and CBL, the review offers a balanced account and proposes an E–I–P–R alignment and a research agenda for longitudinal, multi-site, moderator-sensitive studies.